Factors Affecting the Plagiarism Behavior of Faculties in Maharashtra - Linge, Ashish; Bapte, Vishal Dattatray; Kakde, Baldeo (DESIDOC Journal of Library & Information Technology, 2023)
The study aims to determine the impact of awareness, knowledge, and attitude toward plagiarism on the plagiarism activity of college teachers in Maharashtra State, India. Two hundred seventy-two college teachers within Maharashtra State, India, participated in the survey. The study used purposive and snowball sampling techniques. The college teachers have a reasonable awareness and moderate knowledge of plagiarism. The college teachers bore a positive attitude toward plagiarism. The results of multiple regression analysis showed a significant influence of all three independent variables on the plagiarism activities of college teachers. Attitude towards plagiarism was forecasted as the highest predictor of plagiarism activities of college teachers, followed by knowledge of plagiarism.